2007
DOI: 10.1152/ajpgi.00324.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle and apoptosis regulatory protein-1: a novel regulator of apoptosis in the colonic mucosa during aging

Abstract: Cell cycle and apoptosis regulatory protein-1: a novel regulator of apoptosis in the colonic mucosa during aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Earlier, as has been observed in the current investigation, the age-related increase in the expression of several markers of CSLC in the colonic mucosa is associated with a concomitant increase in EGFR expression, and these increases are exacerbated by DMH (16,34). Aging has also been shown to be associated activation of EGFR and its downstream signaling events (20,21). Our current data further demonstrate that administration of cetuximab, monoclonal antibodies to EGFR that inhibit EGFR activation, not only inhibits the expression of CSLC markers CD166 and ALDH-1 but also miR-21 expression in the colonic mucosa in both young and aged animals, but the magnitude of inhibition of these parameters is much greater in aged than that noted in young animals.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Earlier, as has been observed in the current investigation, the age-related increase in the expression of several markers of CSLC in the colonic mucosa is associated with a concomitant increase in EGFR expression, and these increases are exacerbated by DMH (16,34). Aging has also been shown to be associated activation of EGFR and its downstream signaling events (20,21). Our current data further demonstrate that administration of cetuximab, monoclonal antibodies to EGFR that inhibit EGFR activation, not only inhibits the expression of CSLC markers CD166 and ALDH-1 but also miR-21 expression in the colonic mucosa in both young and aged animals, but the magnitude of inhibition of these parameters is much greater in aged than that noted in young animals.…”
Section: Discussionsupporting
confidence: 79%
“…Our current data further demonstrate that administration of cetuximab, monoclonal antibodies to EGFR that inhibit EGFR activation, not only inhibits the expression of CSLC markers CD166 and ALDH-1 but also miR-21 expression in the colonic mucosa in both young and aged animals, but the magnitude of inhibition of these parameters is much greater in aged than that noted in young animals. Whether other members of the EGFR, specifically HER-2 and HER-3, which are also activated in the aging colon (21) and are known to play critical roles in the development and progression of many epithelial malignancies, including the colorectal cancer, play a role in the development of the CSLC phenotype remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The two proteins whose function in humans is to inhibit apoptosis, CAS and IAP, were significantly down-regulated by about 2-fold, yet apoptotic processes were not inhibited, at least after 2 d of feeding. The fact that CARP, a protein generally associated with an increase in apoptosis [63], did not respond to the diet suggests that there was no clear apoptosis induction in adult females in our experimental conditions. Buttino et al [64] using aldehyde-encapsulating liposomes observed apoptotic regions in copepod female gonads only after 9 d of feeding.…”
Section: Discussionmentioning
confidence: 80%
“…In fact, the occurrence of both nonmalignant and malignant colorectal neoplasm increases with advancing age (4). Although the reasons for this increase is not fully understood, results from animal experimental models show that aging is associated with increased proliferation and attenuated apoptosis in both gastric and colonic mucosa, leading to increased susceptibility to cancer (5). This has in part been attributed to increased expression and activation of epidermal growth factor receptor (EGFR) and its family members in the gastrointestinal (GI) mucosa (4).…”
Section: Introductionmentioning
confidence: 99%